The Impact of Digital Money on Business Dynamics: The Main Role of Information Systems Technology - M.Sahlan; Muhammad Irwan Padli Nasution (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Economic development in the world sector, especially in Indonesia, cannot be separated from information systems. Digital money changes the way financial transactions are issued, improving business processes, increasing market security, and reducing the burden of international trade. Digital currencies also enable business model innovations such as subscription payments, ecosystem platforms, and the sharing economy, which are changing the way companies communicate with consumers and partners. Not only support secure financial transactions, but also enable in-depth data analysis. This triggers the creation of valuable insights for companies in understanding consumer behavior, market trends and new growth opportunities. Apart from that, the existence of a reliable information system also expands financial accessibility, especially for those who previously did not have access to formal banking services. This kind of financial inclusion can empower society and open up wider economic opportunities, creating a more equitable impact on economic growth supported by digital money.The main task of information technology systems in this case is to provide safe, reliable and efficient infrastructure to support digital currency-based business activities.